PSIX-31 Early postmortem pH and glycogen content, and their association with meat quality traits in grass-fed steers. (7th December 2018) - Jerez-Timaure, N; Brickmann, G; Ramirez, A; Strobel, P; Berkhoff, M
Abstract: From a contemporary group of crossbred Angus and Friesian crossbred steers (n=70) raised only with pasture (age approximately 24 mo), 30 carcasses were selected to investigate how the variation in early postmortem pH and glycogen content in longissimus lumborum (LL) muscle affect meat quality traits. Muscular pH and core LL samples were measured and obtained at 3, 6 and 24 h postmortem. Additionally, based on pHvalues at 3h (pH3h ), carcasses were segregated as follow: low ((6.2 to 6.5), and high(>6.5), obtaining 10 carcass/group. At 48 h postmortem, LL steaks were obtained to evaluate objective color ( L *, a * and b * values), shear force, cooking loss and drip loss. One-way ANOVA test was performed for normal distribution data and Friedman ANOVA for nonparametric data; additionally, correlations analysis was made using Spearman correlation coefficient. The ANOVA determined that meat quality traits were not affected by pH3h groups (P >0.05). Similar results were found with correlation analysis; pH3h valueswere not correlated( P >0.05) with any of the meat quality traits; however, pH at 24h postmortem showed a significant a negative (P < 0.05) correlation with L* (r= -055), a* (r= -0.591) and b* (r= -0.58). On the other hand, glycogen content from samples taken at 3 hr postmortem showed a moderate and positive association ( P 0.05) with any variable measured. The preliminary results indicate that glycogen content measured at early postmortem could be an accurate predictor of meat quality rather than pHvalues, which will help to improve the early detection of dark cutting meat in grass-fed steers.